On motivation of phraseological units – pisz na Berdyczów - Kosek, Iwona (Papers in Linguistics, 2021)
The article is an attempt to describe the motivation (as understood by A. M. Lewicki) of a slightly forgotten Polish phraseological unit – pisz na Berdyczów (used when a speaker wants to get rid of someone: lit. ‘write to Berdyczów’; Berdyczów – a city in Ukraine). The first part of the article contains a few remarks on the structure and meaning of the unit, while its second part discusses motivation. The author presents possible hypotheses related to the motivation of the unit, suggesting that the connotations with Berdyczów as an unknown remote place are most important for the contemporary understanding of the analysed phraseological unit.